The cycling mode share in cities. - (:unkn) unknown (My University, 2012)
The cycle mode share is an important indicator for the relevance of cycling in a city/town or municipality. It is influenced by a variety of factors; their impacts are hard to differentiate and quantify. There is clear evidence, however, that policy-makers can bring about significant positive changes through systematic and consistent cycling promotion. In order to underpin and evaluate such political measures, sound methods are needed to assess and explain bicycle use. (Difu)
Keywords: Individualverkehr; Fahrradverkehr; Stadtverkehr; ÖPNV; Fußgänger; Autoverkehr; Erhebungsmethode; Modal Split; Mobilitätsverhalten; Fahrradnutzung; Fahrradbenutzung